Experimental study on piles as settlement reducers in modeled piled raft - Muhd Luqman Nul Hakim Mohd Ghazalie. (2012)
This study examines the effect of piled raft and raft resting on pile reinforced sand. A total of 20 tests were conducted throughout the process. The 2 main experimental set up were carried out using rafts using varying number of piles, lengths and diameter. The results were compared with the results of free standing pile groups and plain raft to study the effects such as load settlement and stiffness.